2019
DOI: 10.1111/petr.13357
|View full text |Cite
|
Sign up to set email alerts
|

Various initial presentations of Epstein‐Barr virus infection‐associated post‐transplant lymphoproliferative disorder in pediatric liver transplantation recipients: Case series and literature review

Abstract: PTLD is a rare but potentially life‐threatening condition, which shows a higher prevalence in children than in adults. From 129 children who underwent LT, we reported 5 cases with biopsy‐proven PTLD at a single teaching hospital. Four patients had shared clinical presentations including fever, lymphadenopathy, and splenomegaly. They were noted to be given a prolonged course of IS due to the management of comorbid complications such as acute cellular rejection or severe food allergy or eosinophilic gastrointest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The panel provided further clarity on the limited information obtained from the target literature review. Overall, articles used for survey development indicated that patients with EBV + PTLD are at a significant risk of treatment-related toxicity and mortality when undergoing chemotherapy [ 21 , 28 32 ]. Chemotherapy also increases the risk of post-treatment infection and can exacerbate GvHD in EBV + PTLD following HCT [ 33 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The panel provided further clarity on the limited information obtained from the target literature review. Overall, articles used for survey development indicated that patients with EBV + PTLD are at a significant risk of treatment-related toxicity and mortality when undergoing chemotherapy [ 21 , 28 32 ]. Chemotherapy also increases the risk of post-treatment infection and can exacerbate GvHD in EBV + PTLD following HCT [ 33 35 ].…”
Section: Discussionmentioning
confidence: 99%